Cheap Genes and Academic Conflict (The Scientific World Journal)
A story about a German research group that supplies free genes leads off the news in Nature this week. Science leads with a story about academics who are offended by a recent suggestion by the US government that they disclose “institutional conflicts of interest” in scientific research.